2015
DOI: 10.1007/s00264-015-2881-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between multiple cannulated screws and dynamic hip screw for fixation of femoral neck fracture in adults

Abstract: It seems to us that in our practice the fixation of femoral neck fracture in young adults with the DHS is a better option compared with the osteosynthsis with multiple cannulated screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…Bonnaire et al 15 also advocated DHS against MCS in high shear angle neck fractures. Siavashi et al, 33 Razik et al, 34 and Gardner et al 35 also agree that DHS is a better option compared with cannulated screws. Addition of a derotational screw placed in the cranial part of the femoral neck superior to the dynamic hip screw can improve the rotational stability of the construct.…”
Section: Discussionmentioning
confidence: 92%
“…Bonnaire et al 15 also advocated DHS against MCS in high shear angle neck fractures. Siavashi et al, 33 Razik et al, 34 and Gardner et al 35 also agree that DHS is a better option compared with cannulated screws. Addition of a derotational screw placed in the cranial part of the femoral neck superior to the dynamic hip screw can improve the rotational stability of the construct.…”
Section: Discussionmentioning
confidence: 92%
“…However, comparison between these two fixation methods has to be dealt with caution due to small patient numbers. Siavashi and colleagues found a lower rate of fixation failure of DHS compared to cancellous screws for the treatment of femoral neck fractures [ 18 ]. Another study failed to show significant differences between both treatment options [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that there was a substantial difference in implant survival between the treatment groups, with the SHS superior to cannulated screws when internal fixation is used. According to the current literature, the stability of SHS fixation is superior to cannulated screws, particularly in vertical and basal fractures, which are more unstable [11][12][13][14]. Our results suggest that stable fixation may be more important in ADS patients, as many trauma patients continue to drink after sustaining an injury and thus may be less likely to follow mobility restrictions during postoperative rehabilitation [15,16].…”
Section: Discussionmentioning
confidence: 61%